An insight into the viscosity prediction of ternary alloys with limited solubility. Issue 19 (2nd October 2019) - Yu, Zhi-Gang; Luo, Qun; Zhang, Jie-Yu; Chou, Kuo-Chih
ABSTRACT: Geometrical models have been successfully applied into the calculation of viscosity of alloys. However, traditional geometrical (TG) models are feasible only in systems with a complete solubility area. Otherwise, they will not work. In this paper, a new method has been introduced for the calculation of alloy systems with limited solubility. How the new method overcomes the drawbacks of the TG models is discussed and analysed. The viscosity of two alloy systems with limited solubility is calculated by the present model. Comparisons between the experimental viscosity and the calculated values by different models show that our model gives the best results, especially for the data nearby the limited solubility area. The introduction of this model provides a way to solve the calculation problems of ternary alloys with limited solubility, which will extend geometrical models to more practical systems.